The Role of Kyai and the State in Regulating Child Marriage: A Study in Cirebon Regency - Muhammad Sibawaihi; Nandang Najmudin; Abdul Kholik; Muhammad Yogi Sandra (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Child marriage remains a pressing socio-legal issue in Indonesia, where religious norms often intersect and sometimes conflict with state regulations. This study explores the dynamic interaction between kyai (Islamic religious leaders) and state authorities in regulating child marriage within Cirebon Regency—a region known for its strong pesantren-based traditions. Using a qualitative case study approach, data were collected through in-depth interviews with kyai, judges, and families, supported by observations and document analysis of court rulings, religious texts, and local socio-cultural practices. The findings reveal that most kyai continue to legitimize child marriage through classical fiqh doctrines such as darūrah syar‘iyyah (religious necessity) and maslahah (public interest), reflecting the enduring influence of traditional interpretations. However, younger kyai are beginning to adopt contextual ijtihād that aligns with contemporary child protection principles under maqāṣid al-sharī‘ah. Meanwhile, state institutions struggle to implement the 2019 Marriage Law effectively due to the strong moral authority held by kyai. This study contributes to the field of contextualized Islamic law by developing a model of legal harmonization that integrates maqāṣid-based reinterpretation of fiqh with Indonesia’s child protection framework. The research offers both theoretical insight—by advancing the discourse on critical legal pluralism in Muslim societies—and practical guidance for policymakers to foster collaboration between religious leaders and state institutions in preventing child marriage while respecting local religious values.